Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Sure, let's break this down step-by-step using the given initial conditions and recursive rule.
### Step 1: Calculate [tex]\( P_1 \)[/tex] and [tex]\( P_2 \)[/tex]
The initial population is given as:
[tex]\[ P_0 = 70 \][/tex]
The recursive rule for the population is:
[tex]\[ P_n = P_{n-1} + 30 \][/tex]
Using this rule:
1. For [tex]\( P_1 \)[/tex]:
[tex]\[ P_1 = P_0 + 30 \][/tex]
Since [tex]\( P_0 = 70 \)[/tex]:
[tex]\[ P_1 = 70 + 30 = 100 \][/tex]
2. For [tex]\( P_2 \)[/tex]:
[tex]\[ P_2 = P_1 + 30 \][/tex]
Since [tex]\( P_1 = 100 \)[/tex]:
[tex]\[ P_2 = 100 + 30 = 130 \][/tex]
### Step 2: Find an explicit formula for the population
To find the explicit formula, let's observe the pattern in the population growth:
- [tex]\( P_1 = 100 \)[/tex]
- [tex]\( P_2 = 130 \)[/tex]
- Generally, each step increases the population by 30.
This can be generalized as follows:
[tex]\[ P_n = P_0 + n \cdot 30 \][/tex]
Thus, the explicit formula for the population is:
[tex]\[ P_n = 70 + 30n \][/tex]
### Step 3: Use the explicit formula to find [tex]\( P_{100} \)[/tex]
Now we will use the explicit formula to find [tex]\( P_{100} \)[/tex]:
[tex]\[ P_{100} = 70 + 30 \cdot 100 \][/tex]
[tex]\[ P_{100} = 70 + 3000 \][/tex]
[tex]\[ P_{100} = 3070 \][/tex]
To summarize:
[tex]\[ \begin{array}{l} P_1 = 100 \\ P_2 = 130 \\ \end{array} \][/tex]
The explicit formula for the population is:
[tex]\[ P_n = 70 + 30n \][/tex]
Finally, the population at [tex]\( n = 100 \)[/tex] is:
[tex]\[ P_{100} = 3070 \][/tex]
### Step 1: Calculate [tex]\( P_1 \)[/tex] and [tex]\( P_2 \)[/tex]
The initial population is given as:
[tex]\[ P_0 = 70 \][/tex]
The recursive rule for the population is:
[tex]\[ P_n = P_{n-1} + 30 \][/tex]
Using this rule:
1. For [tex]\( P_1 \)[/tex]:
[tex]\[ P_1 = P_0 + 30 \][/tex]
Since [tex]\( P_0 = 70 \)[/tex]:
[tex]\[ P_1 = 70 + 30 = 100 \][/tex]
2. For [tex]\( P_2 \)[/tex]:
[tex]\[ P_2 = P_1 + 30 \][/tex]
Since [tex]\( P_1 = 100 \)[/tex]:
[tex]\[ P_2 = 100 + 30 = 130 \][/tex]
### Step 2: Find an explicit formula for the population
To find the explicit formula, let's observe the pattern in the population growth:
- [tex]\( P_1 = 100 \)[/tex]
- [tex]\( P_2 = 130 \)[/tex]
- Generally, each step increases the population by 30.
This can be generalized as follows:
[tex]\[ P_n = P_0 + n \cdot 30 \][/tex]
Thus, the explicit formula for the population is:
[tex]\[ P_n = 70 + 30n \][/tex]
### Step 3: Use the explicit formula to find [tex]\( P_{100} \)[/tex]
Now we will use the explicit formula to find [tex]\( P_{100} \)[/tex]:
[tex]\[ P_{100} = 70 + 30 \cdot 100 \][/tex]
[tex]\[ P_{100} = 70 + 3000 \][/tex]
[tex]\[ P_{100} = 3070 \][/tex]
To summarize:
[tex]\[ \begin{array}{l} P_1 = 100 \\ P_2 = 130 \\ \end{array} \][/tex]
The explicit formula for the population is:
[tex]\[ P_n = 70 + 30n \][/tex]
Finally, the population at [tex]\( n = 100 \)[/tex] is:
[tex]\[ P_{100} = 3070 \][/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.